Media Frame Building and Culture: Transgenic crops in two Brazilian Newspapers during the “Year of Controversy” - Massarani, Luisa; Brossard, Dominique; Almeida, Carla; Buys, Bruno; Lewis, Emily Acosta (E-Compós, 2013)
Brazil is the second world producer of transgenic crops. However, intense controversies were around their introduction in the country. This study analyzes media coverage of GM crops in two elite Brazilian newspapers, Folha de S. Paulo and O Globo, in 2003, the “Year of Controversy”, a period of intense political debate over the issue. Using issue attention cycle and media frame building as theoretical frameworks, we combine quantitative content analysis and in-depth individual interviews with journalists to identify the main influencers of media coverage. Our study revealed that the two newspapers covered the issue differently than in the United States. North American newspapers tended to emphasize dramatic elements when the GM issue was discussed in the political arena; in Brazil, technical elements were a major focus in the stories. Keywords Transgenic crops. Content analysis. Attention cycle. Media frame building. Newspapers. —————————— RESUMO (Português): O Brasil é o segundo produtor mundial de cultivos transgênicos. No entanto, houve intensa controvérsia em torno da introdução de tais plantações no país. Este estudo analisa a cobertura dos cultivos transgênicos em dois jornais de elite brasileiros, Folha de S. Paulo e O Globo, em 2003, o “Ano da Controvérsia”, período de intenso debate político sobre a questão no país. Utilizamos como referenciais teóricos ciclo de atenção e construção de frame mediático, associando análise quantitativa de conteúdo e entrevistas em profundidade com jornalistas visando identificar os principais fatores que influenciaram a cobertura jornalística. Nosso estudo revelou que os dois jornais cobriram o tema de forma diferente do que ocorreu nos Estados Unidos. Os jornais norte-americanos tenderam a enfatizar elementos dramáticos quando a questão dos transgênicos era discutida na arena política; no Brasil, elementos técnicos foram um foco principal nas matérias. Palavras-chave Cultivos transgênicos. Análise de conteúdo. Ciclo de atenção. Frame mediático. Jornais diários.